2014
DOI: 10.1364/boe.5.002009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of temporal vascular effects induced by focused ultrasound treatment with speckle-variance optical coherence tomography

Abstract: Focused ultrasound (FUS) can be used to locally and temporally enhance vascular permeability, improving the efficiency of drug delivery from the blood vessels into the surrounding tissue. However, it is difficult to evaluate in real time the effect induced by FUS and to noninvasively observe the permeability enhancement. In this study, speckle-variance optical coherence tomography (SVOCT) was implemented for the investigation of temporal effects on vessels induced by FUS treatment. With OCT scanning, the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…During this BBB-opened process, transient vessel/capillary dilation has been observed previously via two-photon microscopy, and also contributes to this ultrasound-microbubble interacted mechanical-stress localized amplification on capillary lumen [8,9]. Previously, it has been pointed out that the morphological change was resulted from the mechanical stress due to FUS exposure and the results revealed that such deformation can be identified with OCT [19,20]. Therefore, we proposed to use OCT as a potential tool to in-vivo monitor and evaluate the induced cerebral effects.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…During this BBB-opened process, transient vessel/capillary dilation has been observed previously via two-photon microscopy, and also contributes to this ultrasound-microbubble interacted mechanical-stress localized amplification on capillary lumen [8,9]. Previously, it has been pointed out that the morphological change was resulted from the mechanical stress due to FUS exposure and the results revealed that such deformation can be identified with OCT [19,20]. Therefore, we proposed to use OCT as a potential tool to in-vivo monitor and evaluate the induced cerebral effects.…”
Section: Discussionmentioning
confidence: 55%
“…ICR mice (male, 7-8 weeks old) were employed. The experimental procedures are similar to our previous studies [19,20]. Prior to FUS exposure, animals received anesthesia (10% isoflurane); then craniotomy was performed (the cranial bone of 5 mm dimension was removed) in order to eliminate the issue of focal beam aberration and energy distortion caused by skull bone, as well as optical attenuation.…”
Section: Animal Preparation and Experimental Designmentioning
confidence: 99%
“…These smallest microvessels are difficult to detect otherwise, yet are important of early pathology detection and treatment response monitoring. 31 Further, as MB-based OCT contrast appears to decrease with flow velocity, this methodology may potentially help visualize stationary (no blood flow) conditions as blocked/stagnant microvessels amongst the flowing microvascular network, thus isolating dysfunctional perfusion foci that are otherwise difficult to detect. These findings warrant further investigations in utilizing MB for tissue hemodynamic investigations and for microvasculature contrast enhancement in OCT angiography.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of these image pre-processing steps was fairly modest and direct, compared to the more extensive and more subjective set of operations and transformations (e.g., binarization, skeletonization, etc.) that are needed for analytical metrics derivations 9 , 13 16 . The resultant microvascular images were then grouped for AI analysis.…”
Section: Methodsmentioning
confidence: 99%